2007
DOI: 10.1002/pri.384
|View full text |Cite
|
Sign up to set email alerts
|

Is mechanical pain threshold after transcutaneous electrical nerve stimulation (TENS) increased locally and unilaterally? A randomized placebo‐controlled trial in healthy subjects

Abstract: TENS administered at a strong but comfortable non-painful stimulation intensity increases mechanical pain threshold ipsi-laterally in healthy subjects, whereas TENS administered at sensory threshold intensity does not. TENS may be ineffective if electrodes are placed contralaterally or distant to the pain site and if stimulation intensity levels are not titrated to subjective strong levels. Further clinical trials are needed to clarify if these findings may also be generalized to populations of chronic pain su… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
39
0
1

Year Published

2009
2009
2017
2017

Publication Types

Select...
7
3

Relationship

2
8

Authors

Journals

citations
Cited by 80 publications
(51 citation statements)
references
References 24 publications
8
39
0
1
Order By: Relevance
“…Electrophysiological studies show that inhibition of central nociceptive cells disappears within minutes during low-amplitude TENS but may last over 1 hour when TENS intensity is increased to recruit higher threshold afferents (ie, A-d and C-fibres). [43][44][45][46][47] The findings of studies 5,14,15,22,24,48 using experimentally induced pain suggest that low-intensity TENS is rapid in onset and offset, returning to baseline within 20 minutes of TENS switch off although 1 study 49 found that the time to maximum effect may take 30 minutes. We have been unable to find any convincing evidence from experimental pain studies that low-intensity TENS given at low frequency differs in poststimulation duration from low-intensity TENS given at high frequencies.…”
Section: Discussionmentioning
confidence: 99%
“…Electrophysiological studies show that inhibition of central nociceptive cells disappears within minutes during low-amplitude TENS but may last over 1 hour when TENS intensity is increased to recruit higher threshold afferents (ie, A-d and C-fibres). [43][44][45][46][47] The findings of studies 5,14,15,22,24,48 using experimentally induced pain suggest that low-intensity TENS is rapid in onset and offset, returning to baseline within 20 minutes of TENS switch off although 1 study 49 found that the time to maximum effect may take 30 minutes. We have been unable to find any convincing evidence from experimental pain studies that low-intensity TENS given at low frequency differs in poststimulation duration from low-intensity TENS given at high frequencies.…”
Section: Discussionmentioning
confidence: 99%
“…Using the strongest intensity that remains comfortable produces hypoalgesia in healthy subjects; lower intensities are ineffective [4956]. In addition to activation of greater numbers of sensory afferents, higher pulse amplitudes are proposed to activate deeper tissue afferents allowing for greater analgesia [2].…”
Section: Factors That Directly Affect Tens Efficacymentioning
confidence: 99%
“…It was suggested that the intensity of electrical stimuli should be titrated to enough extent to achieve maximum analgesic effect. 42,43) A recent systemic review reported that while moderate evidence of efficacy was reported for intense TENS, conventional TENS had overall conflicting evidence of efficacy and TENS with low-intensity and low-frequency had the lack of efficacy, which may be linked with an insufficient stimulus to active nerve fibers.…”
Section: Pulse Intensitymentioning
confidence: 99%